Species Diversity of Dragonfly in Rawa Danau Nature Reserve Serang Banten as a field Guide Book Based Conservation Education - Rachmawati, Rizqi Nur; Mukti, Suroso; Mahrawi, Mahrawi (BIOEDUKASI, 2024)
This research aims to determine species diversity of dragonflies at the Rawa Danau Nature Reserve. The methodology of this research is an exploration of collecting data techniques using the sweeping net. This research was held in January to December. Sampling was done with 2 sessions are 09.00-11.00 WIB and 15.00-17.00 WIB with three times repetition each session. Sampling was done at two places especially in Sukatani and Cikedung. The procedures of this research are samples were taken by insect net and the abiotic components were calculated such climatic (humidity, air temperature, light intensity, wind velocity) edaphic (soil moisture, soil Ph). Based on the results, Sukatani obtained a diversity index was 1.98 and Cikedung was 2.46 with both categories are medium. Then, Sukatani obtained an evenness index was 0.67 and Cikedung was 0.87 with both categories are high. Environmental conditions are in the optimal range for the life of dragonflies. The final results of this research were made as a field guide book based on conservation education species diversity of dragonfly at Rawa Danau Nature Reserve with a score of expert test assessment obtained 80,39% with the category is good as an educative reading source.